ANALYSIS OF METAPHORICAL EXPRESSIONS USED IN THE BOOK ENTITLED SHAKESPEARE PROVERBS INSCRIBED BY MARY COWDEN CLARKE - Rizky Saraan; Clara A. Mamentu; Sarah Kamagi (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2021)
The aims of the research are to find out ontological metaphors in Shakespeare’s proverbs, and to interpret the meaning of those metaphors. The data are taken from the book entitled Shakespeare proverbs inscribed by Mary Cowden Clarke. This research is a qualitative research. In collecting the data, the documentation technique is used in this research. The steps that the researchers have taken in order to collect the data are: reading the Shakespeare proverbs book, marking the proverbs that identified as ontological metaphor, interpreting the meaning of those metaphors. The data are categorized analysed based on George Lakoff and Mark Johnson theory. In analysing the data, the three steps conducted by Miles and Huberman are used in this research, they are: data reduction, data display and data verification/conclusion. The result from this research shows that there are 44 proverbs in Shakespeare Proverb book that contained ontological metaphors. This research is suggested to be a reference for the readers and the other researchers in order learning and interpreting metaphorical expressions in proverbs or the other literature works Keywords: Metaphorical Expression, Proverb